2019
DOI: 10.1017/aap.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Computational Photography, 3-D Modeling, and Online Publication of Basketry for Cache Cave, California

Abstract: Advanced 2-D and 3-D computer visualizations are increasingly being used for recording and documentation, analysis, dissemination, and public engagement purposes. Recent technological advances not only considerably improve data acquisition, processing, and analysis but also enable easy and efficient online presentation. This article evaluates the contributions of advanced 2-D and 3-D computer visualization and discusses the potential of 3-D modeling for recording basketry technology and documenting the state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In a similar case study, Andreu and Serrano (2019) showed how photogrammetry of stellae and the virtual manipulation of model attributes—including the generation of height maps—can improve readability of weathered or damaged inscriptions. Integrating virtual reconstruction of pottery and designs with other techniques like D-stretch on pottery (González et al 2019) and reflectance transformation imaging with basketry (Kotoula et al 2019), archaeologists developed techniques to visualize designs that had degraded. Other studies matched 3D models derived from photogrammetry with principal component analysis, allowing the complete estimated reconstruction of ceramic vessels (Zvietcovich et al 2016).…”
Section: Object-based Photogrammetrymentioning
confidence: 99%
“…In a similar case study, Andreu and Serrano (2019) showed how photogrammetry of stellae and the virtual manipulation of model attributes—including the generation of height maps—can improve readability of weathered or damaged inscriptions. Integrating virtual reconstruction of pottery and designs with other techniques like D-stretch on pottery (González et al 2019) and reflectance transformation imaging with basketry (Kotoula et al 2019), archaeologists developed techniques to visualize designs that had degraded. Other studies matched 3D models derived from photogrammetry with principal component analysis, allowing the complete estimated reconstruction of ceramic vessels (Zvietcovich et al 2016).…”
Section: Object-based Photogrammetrymentioning
confidence: 99%